Evaluación Financiera en el “Comercial Pineda” de la Ciudad de Loja, en el Periodo 2014-2015 - Vélez Quizhpe, Mayra Elizabeth (2017)
The thesis work entitled FINANCIAL EVALUATION IN THE COMMERCIAL PINEDA OF THE CITY OF SHOP, IN THE PERIOD 2014-2015, was executed according to a general objective: To apply the Financial Assessment in the "Commercial Pineda" of the City of Loja, period 2014 - 2015 ", in order to determine the financial situation of the company, fulfilling the requirements prior to choosing the Degree in Accounting and Auditing, Public Accountant - Auditor, at the National University of Loja, adjusting This form to the Regulations of Academic Regime in force. For the fulfillment of the objectives was "Determined the economic and financial structure to know the different items that intervene in the economic position of the business". It began with the collection of information, from which the vertical and horizontal analysis of the financial statements for the years 2014 - 2015 was carried out, obtaining as a result that the current assets there is a decrease of $ 91,426.01 equivalent to -13.60% and in non-current assets an increase of $320.33, which represents 21.55% due to the depreciation of fixed assets. In current liabilities there is a decrease of $ 99,808.03 which represents 26.56%. This means that the commercial has acquired a long-term bank obligation, as regards non-current liabilities there is an increase of $ 18,172.45, which is 100.00%, which is due to the acquisition of a long - term financial obligation in financial institutions and a decrease of $ 22,724.23, which represents the 7,63% which indicates that this is due to an increase in the usefulness of the exercise the same that can predict incidental cases. In the analysis and revision of the Financial Statements, the indicators that determine the liquidity, indebtedness, activity and profitability are applied, Dupont System, Eva allowed to know the level of operations of the company. Finally, the report of the Financial Assessment was carried out, where conclusions and recommendations are recorded, which will be used to make decisions, in order to inform the results of the Analysis of the Financial Statements for the years 2014 - 2015 the application Of a Financial Assessment of Commercial Pineda; So that it contains suggestions aimed at improving financial management. When carrying out the Financial Assessment of Commercial Pineda, it is concluded that excessive indebtedness with financial institutions and the lack of capacity to cover its short-term obligations, is the cause for having liquidity, which can cause serious inconveniences that do not Allows him to continue with his commercial activity.